Necrotizing Gingivitis: Microbial Diversity and Quantification of Protein Secretion in Necrotizing Gingivitis - Nicolas Gerhard; Thomas Thurnheer; Susanne Kreutzer; Rudolf Dominik Gmür; Thomas Attin; Giancarlo Russo; Lamprini Karygianni (MDPI AG, 2021)
Necrotizing gingivitis (NG) is a necrotizing periodontal disease that differs from chronic gingivitis (CG). To date, both the microbiological causes and the involved host cytokine response of NG still remain unclear. Here, we investigated corresponding interdental plaque and serum samples from two groups of Chinese patients with CG (n = 21) or NG (n = 21). The microbiota were studied by 16S rRNA Illumina MiSeq sequencing of the microbial metagenome and by assessing quantitatively the abundance of the phylum Bacteroidetes, the genus Prevotella and the species T. forsythia, P. endodontalis, and P. gingivalis using fluorescence in situ hybridization (FISH). With respect to the associated host response, the levels of 30 inflammatory mediators were quantified by multiplex immunoassay analysis. Differential microbial abundance analysis of the two disease groups revealed at the phylum level that Proteobacteria accounted for 67% of the differentially abundant organisms, followed by organisms of Firmicutes (21%) and Actinobacteria (9%). At the species level, significant differences in abundance were seen for 75 species of which 58 species were significantly more abundant in CG patients. Notably, the FISH analysis revealed that Bacteroidetes was the most prevalent phylum in NG. The multiplex cytokine assay showed significant quantitative differences between the disease groups for eight analytes (GM-CSF, G-CSF, IFN-α, IL-4, IL-13, TNF-α, MIG, and HGF). The G-CSF was found to be the most significantly increased inflammatory protein marker in NG. The next-generation sequencing (NGS) data supported the understanding of NG as a multi-microbial infection with distinct differences to CG in regard to the microbial composition.